Is Less Really More? The Case for Comprehensive Written Corrective Feedback - Falhasiri, Mohammad (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
An underexplored question, and one with potentially far-reaching implications for the practice of written corrective feedback (WCF), is whether to mark a wide range of errors (comprehensive feedback) or to focus on a few error types (focused feedback) in learners’ L2 writing. Despite limited evidence, it is argued that comprehensive WCF is unsystematic, inconsistent, confusing, and intimidating; can cognitively and affectively overwhelm L2 learners and may dilute attention to WCF. This paper aims to first respond to and call into question these and other arguments against comprehensive WCF, and then it puts forward some arguments against focused WCF. In doing so, it draws on dominant SLA theories and empirical research findings to lend support to the rebuttals and arguments. Some concrete suggestions are made to help teachers fully exploit the potentials of a comprehensive feedback approach.